FACTORS THAT INFLUENCE THE BEHAVIOR OF HOUSEWIVES ON WASTE MANAGEMENT IN CABEAN VILLAGE, SAWAHAN DISTRICT, MADIUN REGENCY - Krisnowo, Kukuh; Nur R, Karina; Ari W, Pipid (Jurnal Kesehatan, 2024)
The behavior of housewives about waste management includes the stage of collecting waste, transportation of waste, waste management, and final disposal. The purpose of this study is to analyze the factors that influence the behavior of housewives on waste management. In this research, the researcher used descriptive quantitative research as approach. The method of research is analytical survey while the type of research is cross sectional. The population of 926 KK and used samples of 139 respondent. The results of the chi-square test showed that there is a significant influence between independent variable which is knowledge (p-value = 0,014), attitude (p-value = 0,032), and infrastructure (p-value = 0,012) to wards the behavior of housewives about waste management. From this study, researchers concluded that there was an influence of knowledge, attitudes, infrastructure on the behavior of housewives about waste management in Cabean Village, Sawahan District, Madiun Regency. Suggestions this research is increasing socialization to the public about waste where the community is required to carry out waste management such as waste collection, waste transportation, waste treatment and the final disposal stage. And conduct more optimal and comprehensive supervision in the community.